UMKM EMPOWERMENT STRATEGIES FOR LOCAL ECONOMIC IMPROVEMENT: A LITERATURE REVIEW - Loso Judijanto; Mohamad Khairi Bin Haji Othman (CV. Adiba Aisha Amira, 2024)
MSME empowerment strategies for local economic improvement demonstrate the important role of MSMEs in driving economic growth at the local level. This study examines various empowerment strategies that include education and training. The results show that education and training improve the skills and capacity of MSME actors, making them better equipped to face business challenges. Easy and flexible access to finance enables MSMEs to make the necessary investments for their business development. In addition, conducive policy and regulatory support from the government is also considered important in creating an enabling environment for MSME growth.